Форми надання правової допомоги - Мартовицька, О. В.; Martovytska, O. V.; Олена Мартовицька (Юридична наука. - 2019. - № 10 (100). - С. 441-446, 2019)
Наголошено, що правова допомога, будучи однією з провідних конституційних гарантій захисту й охорони прав, свобод та інтересів особи в межах відповідних суспільних відносин, може бути надана в декількох формах. Підкреслено, що визначення окремих форм надання правової допомоги має одне з першорядних значень в аспекті встановлення теоретичних і прикладних проблем інституту професійної правничої допомоги в кримінальному процесі.

In the article, it has been emphasized that legal aid, being one of the leading constitutional guarantees for the protection and safeguarding of the rights, freedoms and interests of the individual within the relevant public relations, can be provided in several forms. It has been emphasized that the definition of certain forms of legal aid is of paramount importance in terms of establishing theoretical and applied problems of the institute of professional legal assistance in criminal proceedings. This is due to the fact that the definition of a particular form of provision or type of legal aid will contribute to the most detailed description of the problem that occurs within such forms and types, as a result of which it will be possible to provide the most effective recommendations on possible ways to overcome them. The conceptual and categorical apparatus used in the presented research has been specified. It has been found that the forms of legal aid indicate the external manifestation of such activities, ie how it occurs, while its types – its individual components or directions and methods of its implementation. It has been noted that the forms of legal aid have the appropriate legal basis for their implementation. It has been proposed to understand the form of legal aid as an external expression of such activity enshrined in the provisions of regulations. The positions of scholars have been supported, which distinguish between oral and written forms of legal aid, as well as the representation of the interests of the person concerned. It has been established that by implementing a separate of these forms of legal aid, and in cases provided by current national legislation, a combination of several of them, will be manifested in some of the types of such activities.

Отмечено, что правовая помощь, являясь одной из ведущих конституционных гарантий защиты и охраны прав, свобод и интересов личности в пределах соответствующих общественных отношений, может быть предоставлена ​​в нескольких формах. Подчеркнуто, что определение отдельных форм предоставления правовой помощи имеет одно из первостепенных значений в аспекте установления теоретических и прикладных проблем института профессиональной юридической помощи в уголовном процессе.
Forms of legal aid
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правова допомога; legal aid; правовая помощь; форма; form; форми надання правової допомоги; законодавство; legislation; законодательство; понятійно-категоріальний апарат; conceptual and categorical apparatus; понятийно-категориальный аппарат